Numerical Simulation of Vortex-Induced Transverse Vibration of a Cylinder with Very Low Mass Ratio - Xinxing Zhang; Minghan Hu; Jiancheng Cai; Andrii Babenko; E. Shiju; Zisheng Xu (Shock and Vibration)
Vortex-induced vibration (VIV) of flow past different types of cylinders is important in many engineering fields and has led to a large number of fundamental studies. Computational fluid dynamics (CFD) has become a powerful tool to investigate VIV problems. In this paper, the VIV of an elastically supported rigid-body circular cylinder was numerically studied by solving the Reynolds-averaged Navier–Stokes (RANS) equations with the shear stress transport (SST) k-ω turbulence model. The dynamic mesh approach was used to tackle the domain mesh change due to the cylinder motion. The characteristics of the amplitude response of the cylinder and the vortex shedding frequency at different reduced velocities were compared with the experimental data, and good agreement was found regarding the vibration amplitude and the frequency lock-in phenomenon. Results show the influence of added mass was perceptible in the free vibration and in the initial branch with small cylinder vibration amplitude, while it is fairly weak in the upper and lower branches considering the fact that the main response frequency of the cylinder is close to the natural frequency in a vacuum. Detailed vorticity distributions clearly indicate the 2P vortex modes at the upper and lower branches, and the 2S mode at the initial branch and their generation mechanisms are analyzed. The effects of the cylinder vibration on the lift and drag forces at different branches are discussed, and the frequencies of peak values in their Fourier spectra are examined. The phase difference between the lift force and the cylinder vibration shows an obvious jump from the initial branch to the upper branch with the vortex mode switching from 2S to 2P.